Comparative evaluation of enamel abrasivity of different commercially available dentifrices - An In vitro Study - Rupali Athawale; S K Srinath; Chandralekha Chowdary (Wolters Kluwer Medknow Publications, 2018)
Background: Toothbrushing with toothpaste is a major contributor to dental abrasion. A number of factors such as abrasivity and concentration of the toothpaste, brushing frequency, brushing duration, force of brushing, and toothbrush bristle stiffness have a potential impact on the abrasion process of dental hard tissue. However, the abrasivity of the toothpaste is the most important parameter that affects the abrasion process of dental hard tissue. Aims: This study aims to evaluate the maximum and mean enamel abrasivity of commercially available dentifrices such as Colgate total®, Pepsodent whitening®, Vicco vajradanti®, Dabur red® in primary and permanent teeth. Materials and Methods: Human extracted 60 primary and 60 permanent teeth were randomly selected based on the inclusion criteria. Teeth were sectioned at cementoenamel junction using diamond disc and mounted in an acrylic resin blocks. Baseline profilometric measurements were recorded for all the samples. Four commonly used dentifrices were selected and labeled as Group A (Colgate Total®), B (Pepsodent Whitening®), C (Vicco Vajradanti®), and D (Dabur Red®). Toothpaste slurry was prepared. Tooth specimens were brushed in vitro using a customized brushing machine. After toothbrushing, profilometric measurements were obtained, and the differences in readings served as proxy measure to assess surface abrasion. Data were collected and analyzed using student t-test and ANOVA test. Student t-test was used to compare the enamel abrasivity prebrushing and postbrushing, and ANOVA was used to compare the enamel abrasivity among the four different commercially available toothpastes. Results: In permanent teeth, all the toothpastes were found to cause significant enamel abrasion (P = 0.000) and a significant variation was observed when maximum (P = 0.008) and mean (P = 0.036) enamel abrasivity of these toothpastes were compared. In primary teeth also, all the toothpastes caused significant abrasion (P = 0.000); however, when the maximum and mean abrasivity of these toothpastes were compared, no significant variation was observed (P = 0.438 and 0.163). Conclusions: All the commercially available toothpastes cause significant enamel abrasion. Colgate group caused more enamel abrasion whereas pepsodent caused the least enamel abrasion in permanent teeth.